1987
DOI: 10.1002/jhet.5570240303
|View full text |Cite
|
Sign up to set email alerts
|

Pyrido[2′1′:2,3]imidazo[4,5‐c]isoquinoline and the alkylation of pyrido[2′,1′:2,3]imidazo[4,5‐c]isoquinolin‐5(6H)‐one

Abstract: The reaction of 2‐aminopyridine, o‐phthaldehydic acid and potassium cyanide gave pyrido[2′,1′:2,3]imidazo[4,5‐c]isoquinolin‐5(6H)‐one, which upon treatment with propargylbromide, yielded both O and N alkylated products. 2‐Aminopyridine, o‐phthaldehyde and potassium cyanide gave 1‐cyano‐2‐(2‐pyridyl)isoindole which rearranged in acid to give the previously unreported parent pyrido[2′,1′:2,3]imidazo[4,5‐c]isoquinole. Structures were confirmed using uv, ir, nmr and x‐ray spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This cyano-substituted isoindole 9 was also preliminary prepared by a Strecker-type synthesis between 2-fluoroaniline and o-phthalodicarboxaldehyde in water and in the presence of potassium cyanide and sodium hydrogensulfite 23 . Treatment of 9 with potassium hydroxide in tert-butanol at 80°C led directly to the tetracyclic lactam 4d involving selective hydrolysis to amide, which was able to carry out intramolecular displacement of aromatic fluorine through an anionic ring closure [24][25][26][27] .…”
Section: Chemistrymentioning
confidence: 99%
“…This cyano-substituted isoindole 9 was also preliminary prepared by a Strecker-type synthesis between 2-fluoroaniline and o-phthalodicarboxaldehyde in water and in the presence of potassium cyanide and sodium hydrogensulfite 23 . Treatment of 9 with potassium hydroxide in tert-butanol at 80°C led directly to the tetracyclic lactam 4d involving selective hydrolysis to amide, which was able to carry out intramolecular displacement of aromatic fluorine through an anionic ring closure [24][25][26][27] .…”
Section: Chemistrymentioning
confidence: 99%
“…18 A few procedures have been reported in the literature for the synthesis of pyrido[2 0 ,1 0 :2,3]imidazo [4,5-c]isoquinolines. [19][20][21][22] The most common method for their preparation is the reaction of 2-formylbenzoic acid or its esters, pyridin-2-amines, and KCN, 19 TMSCN/KF 20 or isocyanides. 21,22 In connection with our recent studies on magnetic nanocatalysts in multicomponent reactions, [23][24][25][26][27][28][29] herein, we wish to report the synthesis of pyrido[2 0 ,1 0 :2,3]imidazo [4,5-c]…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only a single example for the formation of this heterocyclic system by a three-component reaction is reported in the literature, namely, the synthesis of pyrido[2‘,1‘:2,3]imidazo[4,5- c ]isoquinolin-5(6 H )-one ( V ) by condensation of 2-aminopyridine, phthaldehydic acid, and potassium cyanide, with only 35% yield. Moreover, the R group at position 6 could be introduced by alkyl halides in a sodium hydride−DMF mixture method, but it is reported that under these conditions an 84:16 mixture of O- and N -alkylated products VI and VII was obtained (Scheme ), which makes it hard to diversify the library.
1 Synthesis of Pyrido[2‘,1‘:2,3]imidazo[4,5- c ]- isoquinolin-5(6 H )-one and its Alkylation Products
…”
mentioning
confidence: 99%